ANALISIS POTENSI AGROINDUSTRI OLAHAN SINGKONG DI KABUPATEN BOJONEGORO - Nuning Setyowati (UII, 2012)
Bojonegoro is one of regency in East Java which attempt to develop the economic condition. An effort is being actively developed is agroindustry based raw materials locally. One of the many commodities produced is cassava. This study aims to map the potential of agroindustry processed cassava and formulate development strategies of processed cassava agroindustry. This study uses descriptive analytical method by using primary data in the form of the potential of agroindustry data and data of leading agroindustry strategic factors. Method of Comparison Exponential (MCE) and Borda method was used to rank the agroindustry potention and SWOT analysis was used to formulate the development strategies of processed cassava agroindustry. The results showed that based on the analysis of MCE, processed cassava agroindustry spread in 15 sub district, they are: Balen, Bubulan, Dander, Gondang, Kadewan, Kalitidu, Malo, Margomulyo, Ngasem, Purwosari, Sekar, Sumberrejo, Tambakrejo, Temayang and Trucuk. Based on Borda analysis showed that processed cassava agroindustry is the fourth leading agroindustry in Bojonegoro. Processed cassava agro-ndustry development strategies include: Improved volume and diversification of processed cassava products, increase product quality based on product quality, packaging innovations marketable, post-harvest training and product safety, maintain continuity of raw materials through cooperation with farmers' groups, introduction of machine dryer according to the needs of craftsmen. Keywords: processed cassava agroindustry, method of comparison exponential, borda, SWOT, Bojonegoro